SYNTHESIS, ANTICANCER ACTIVITY, MOLECULAR DOCKING, AND ABSORPTION, DISTRIBUTION, METABOLISM, AND EXCRETION TOXICITY STUDIES OF NOVEL BENZOTHIAZINES - Jayapriya, Mohan; Ali Muhammad, Sulaiman; Ravi, Subban (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: A series of benzothiazine compounds were studied for absorption, distribution, metabolism, and excretion (ADME) properties to asses their drug-like properties. Compounds 1-10 with favorable ADME properties were selected for molecular docking studies as PIM1 kinase inhibitors. Methods: Synthesis of compound 1 and 7 by conventional heating and characterized by various methods. Molecular docking carried out using Glide software; ADME toxicity predicted using QuickPro. Results: Compound 1 showed a Glide score of âˆ’7.622 kcal/mol with good hydrophobic and hydrophilic interactions with PIM1 kinase proteins and appears to be more potent. Structure-activity relationship study was made among the 10 compounds, and a basic template was arrived at. An analysis of the structure - Affinity relationships suggested that the substituent at position three is important in influencing affinity. Conclusion: Compounds with an alkyl spacer between the carboxyl group and the core benzothiazine ring are required for binding of the compounds with the PIM1 kinase. It was further confirmed by its in vitro anticancer activity of compound 1 against K562 cell lines by 3-(4, 5dimethythiazol-2yl)-2, 5-diphenyl tetrazolium bromide assay by exhibiting an IC 50 value of 36.82 Î¼g/ml. Keywords: Benzothiazine, Molecular docking, Absorption; distribution; metabolism; and excretion properties, In vitro anticancer activity.